Cellular senescence contributes to age‐dependent changes in circulating extracellular vesicle cargo and function. Issue 3 (21st January 2020) - Alibhai, Faisal J.; Lim, Fievel; Yeganeh, Azadeh; DiStefano, Peter V.; Binesh‐Marvasti, Tina; Belfiore, Alyssa; Wlodarek, Lukasz; Gustafson, Dakota; Millar, Sean; Li, Shu‐Hong; Weisel, Richard D.; Fish, Jason E.; et al.
Abstract: Extracellular vesicles (EVs) have emerged as important regulators of inter‐cellular and inter‐organ communication, in part via the transfer of their cargo to recipient cells. Although circulating EVs have been previously studied as biomarkers of aging, how circulating EVs change with age and the underlying mechanisms that contribute to these changes are poorly understood. Here, we demonstrate that aging has a profound effect on the circulating EV pool, as evidenced by changes in concentration, size, and cargo. Aging also alters particle function; treatment of cells with EV fractions isolated from old plasma reduces macrophage responses to lipopolysaccharide, increases phagocytosis, and reduces endothelial cell responses to vascular endothelial growth factor compared to cells treated with young EV fractions. Depletion studies indicate that CD63 + particles mediate these effects. Treatment of macrophages with EV‐like particles revealed that old particles increased the expression of EV miRNAs in recipient cells. Transfection of cells with microRNA mimics recapitulated some of the effects seen with old EV‐like particles. Investigation into the underlying mechanisms using bone marrow transplant studies revealed circulating cell age does not substantially affect the expression of aging‐associated circulating EV miRNAs in old mice. Instead, we show that cellular senescence contributes to changes in particle cargo and function. Notably, senolytic treatment of old mice shifted plasma particle cargo and function toward that of a younger phenotype. Collectively, these results demonstrate that senescent cells contribute to changes in plasma EVs with age and suggest a new mechanism by which senescent cells can affect cellular functions throughout the body. Abstract : Senescent cells accumulate in the body with aging and alter circulating extracellular vesicle microRNA content. This can be replicated in young mice by inducing senescence using sub‐lethal irradiation. Conversely, removal of senescent cells in aged mice by senolytic treatment restores circulating extracellular vesicle microRNA expression to that of a younger phenotype.